THE LEGAL PROTECTION FOR CONSUMERS IN THE PURCHASE OF BAKERY PRODUCTS BASED ON THE CONCEPT OF MAQĀṢID SYARI’AH: A Case Study in Banda Aceh, Indonesia - T. Habibi; Mahdalena Nasrun; Zaiyad Zubaidi (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2026)
This study was motivated by the rapid development of the bakery industry in Banda Aceh, which has not been fully accompanied by the fulfillment of the obligation to provide product information to consumers. Problems arise when bakery products still lack important information, such as ingredient composition, expiry date, and a halal label, thereby potentially posing health risks, harming consumers, and contradicting the principles of consumer protection. This study examines the practice of providing bakery product information to consumers in Kuta Alam District, Banda Aceh, the forms of consumer protection implemented by business actors, and their conformity with the concept of maqāṣid al-syarī‘ah. This study uses a qualitative method with field research. Primary data was obtained through interviews with business actors and bakery employees. In contrast, secondary data was sourced from the Consumer Protection Law, sharia economic law literature, scientific journals, and other written sources relevant to the concept of maqāṣid al-syarī‘ah. The results show that most bakery business actors have not met the standards of information transparency and food safety, resulting in information asymmetry between producers and consumers. These practices are not in line with the principles of maqāṣid al-syarī‘ah, particularly in the aspects of ḥifẓ al-nafs, ḥifẓ al-‘aql, and ḥifẓ al-māl. This study concludes that consumer protection for bakery products in Kuta Alam Subdistrict remains suboptimal, requiring increased awareness among business actors, strengthened government supervision, and the internalisation of Islamic business ethics to realise food safety, honesty, and public welfare.